Self-assessment of driving style and the willingness to share personal information - Carlo Pugnetti; Sandra Elmer (Journal of Risk and Financial Management, 2020)
The availability of better behavioral information about their customer portfolios holds the promise for different and more accurate pricing models for insurers. Changes in pricing, however, are always fraught with danger for insurers, as they enter long-term commitments with incomplete historical information. On the other hand, sharing personal information is still viewed with skepticism by consumers. Which type of personal information are consumers willing to share with insurers, and for what purpose? How would they like to be rewarded for this openness? For insurers, how will the transition shift their risk portfolios? This paper addresses these questions for auto insurance, particularly how the self-assessment of one's driving style impacts this dynamic. In a survey of approximately 900 Swiss residents, we found that offering a compensation, especially premium discounts, but also services, significantly improves willingness to share information. Higher trust in insurance increases sharing. Women and younger people are more willing to share information. On the other hand, customers are less willing to disclose, to insurers, information not traditionally associated with insurance. The self-assessment of driving style also plays a significant role. More risk-averse driving styles are correlated with higher sharing. Conversely, riskier driving styles are correlated with lower sharing. This result is significant for insurers, as new data-driven pricing and services models should tend to attract less risky customer portfolios.
Keywords: 330; behavioral pricing; insurance; self-assessment; sharing information